Analysis of Technological Pedagogical Content Knowledge (TPACK) Ability Based on Science Literacy for Pre-Service Primary School Teachers in Learning Science Concepts - Fakhriyah, F.; Masfuah, S.; Hilyana, F. S.; Mamat, N. (Program Studi Pendidikan IPA Fakultas Matematika dan Ilmu Pengetahuan Alam (FMIPA), 2022)
This study intends to describe and investigate the ability profile of Technological Pedagogy Content Knowledge (TPACK) based on scientific literacy for pre-service primary school teachers. The measurement of student TPACK skills is needed to determine the knowledge of technology that will be implemented in the learning process. Students' TPACK knowledge needs to be developed because integration between pedagogical abilities, material content, and technology is needed. This research is quantitative survey research. This study tested a TPACK model, which was described by the relationship between latent variables, namely from seven components, including TK, PK, CK, TPK, TCK, PCK, and TPACK. The data collection technique used a questionnaire instrument with 46 items. The questionnaire instrument was filled out by 206 pre-service primary school teachers who had taken the Science Concept, Science Application, Science Teaching Learning Course, and Field Experience Practice Courses. The results were then calculated and analyzed using a modeling test with a Structural Equation Modeling (SEM) approach. The results showed that PCK variability could be influenced by the CK and PK components of 51.5%. While the variability of TCK can be influenced by the components of CK and TK of 42.7%. The variability of the TPK can be influenced by the PK and TK components of 45.2%. Finally, the magnitude of the effect of PK, CK, TK, PCK, TPK, and TCK components on TPACK is 61.0%. The TPACK profile of pre-service primary school teachers is good with the factors that contribute most to the components that go into PK and CK. As a result, the findings of this study will contribute to the development of a more thorough profile of the TPACK competencies of pre-service primary school teachers, which can enhance their capacity to incorporate technology when they become teachers in the future.